Chemical constituents from the Tournefortia sibirica L. and their chemotaxonomic significance. (February 2023) - Xue, Yongkang; Zong, Tieqiang; Jin, Long; Li, Junnan; Zhou, Wei; Diao, Shengbao; Li, Gao
Abstract: The phytochemical study of Tournefortia sibirica L. (Boraginaceae) whole plant resulted in the isolation and characterization of 30 compounds, including twelve triterpenoids (1 –12 ), four phenols (13 –16 ), four lignans (17 –20 ), three megastigmanes (21 –23 ), two amides (24 –25 ), two flavonoids (26 –27 ), two sterols (28 –29 ) and one sesquiterpene glucoside (30 ). The structures of these compounds were identified through spectroscopic data analysis and comparison with literature. This is the first report on compounds 3 –16, 18 –19, 21 –25 and 28 from the family Boraginaceae, compounds 1 –2 and 17 from the genus Tournefortia . The chemotaxonomic significance of these compounds was discussed. Graphical abstract: Image 1 Highlights: Thirty chemical constituents were obtained from Tournefortia sibirica L. Twenty-two compounds were reported in the family Boraginaceae for the first time. Three compounds were new for the genus Tournefortia. Chemotaxonomic significance of these compounds was described.